Winter Climate Variability, De-Icing Salt and Streetside Tree Vitality - Miron, Justin; Millward, Andrew A.; Vaziriyeganeh, Maryamsadat; Zwiazek, Janusz J.; Urban, James (Frontiers in Ecology and Evolution, 2022)
The vitality of streetside trees, especially those growing in densely built urban areas, is compromised by repeated exposure to de-icing salts. Such trees already experience unfavourable establishment and growing conditions resulting from poor soil quality, inadequate moisture, physical abuse and air pollutionexposure to de-icing salt aggravates these challenges and can be an essential catalyst in tree mortality. Climate change is creating less predictable weather and, in some cases amplifying the intensity of winter storms. Cities that undertake snow and ice management may adopt modified approaches, and those less familiar with this practice may require its episodic adoption. We identify three pathways by which future climate warming may, counterintuitively, result in cities increasing their use of de-icing salt: (a) warming winter temperatures in cities that were historically too cold to make effective use of sodium chloride (NaCl) for de-icing; (b) cities where daily high temperatures in winter may increase the frequency of freeze-thaw cycles; and, (c) cities in North America and Eurasia that may experience more severe winter weather resulting from greater variability in the circumpolar vortex (CPV). To offset potential damage to existing urban streetside trees and to ensure adequate soil and growing conditions for future trees, there is an immediate need for city foresters to collaborate with traffic safety and public works departments. We present a toolbox of approaches that can facilitate synchronized management efforts, including identifying the location of existing vulnerable trees and re-envisioning future infrastructure that would mitigate tree exposure to de-icing salts.